Home My Page Projects Code Snippets Project Openings diderot

# SCM Repository

[diderot] Diff of /branches/charisee_dev/src/compiler/high-il/normalize-ein.sml
 [diderot] / branches / charisee_dev / src / compiler / high-il / normalize-ein.sml

# Diff of /branches/charisee_dev/src/compiler/high-il/normalize-ein.sml

revision 2450, Thu Oct 3 20:17:08 2013 UTC revision 2605, Wed Apr 30 01:46:09 2014 UTC
# Line 4  Line 4
4      local      local
5
6      structure E = Ein      structure E = Ein
7    (* structure P=Printer*)      structure P=Printer
8        structure F=Filter
9        structure G=EpsHelpers
10
11      in      in
12
13    fun err str=raise Fail (String.concat["Ill-formed EIN Operator",str])
14    val testing=0
15
(*Flattens Add constructor: change, expression *)
|flatten(i,((E.Const c):: l'))=
if (c>0.0 orelse c<0.0) then let
val(b,a)=flatten(i,l') in (b,[E.Const c]@a) end
else flatten(1,l')
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let
val(b,a)=flatten(i,l') in (b,[e]@a) end

val (b,a)=flatten(0,e)
in case a
of [] => (1,E.Const(1.0))
| [e] => (1,e)
(* end case *)
end

(*
fun mkProd [e]=(1,e)
| mkProd(e)=let
fun flatten(i,((E.Prod l)::l'))= flatten(1,l@l')
|flatten(i,((E.Const c):: l'))=
if(c>0.0 orelse c<0.0) then
if (c>1.0 orelse c<1.0) then let
val(b,a)=flatten(i,l') in (b,[E.Const c]@a) end
else flatten(1,l')
else (3, [E.Const(0.0)])
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let
val(b,a)=flatten(i,l') in (b,[e]@a) end
val ( b,a)=flatten(0,e)
in if(b=3) then (1,E.Const(0.0))
else case a
of [] => (1,E.Const(0.0))
| [e] => (1,e)
| es => (b, E.Prod es)
(* end case *)
end

fun mkEps(e)= (case e
of E.Apply(E.Partial [E.V a], E.Prod( e2::m ))=> (0,e)
| E.Apply(E.Partial [E.V a,E.V b], E.Prod( (E.Epsilon(i,j,k))::m ))=>
(if(a=i andalso b=j) then (1,E.Const(0.0))
else if(a=i andalso b=k) then (1,E.Const(0.0))
else if(a=j andalso b=i) then (1,E.Const(0.0))
else if(a=j andalso b=k) then (1,E.Const(0.0))
else if(a=k andalso b=j) then (1,E.Const(0.0))
else if(a=k andalso b=i) then (1,E.Const(0.0))
else (0,e))
|_=> (0,e)
(*end case*))

fun mkApply(E.Apply(d, e)) = (case e
of E.Tensor(a,[])=> (0,E.Const(0.0))
| E.Tensor _=> (0,E.Apply(d,e))
| E.Const _=> (1,E.Const(0.0))
| E.Sub(e2, e3) =>(1, E.Sub(E.Apply(d, e2), E.Apply(d, e3)))
| E.Prod((E.Epsilon c)::e2)=> mkEps(E.Apply(d,e))
| E.Prod[E.Tensor(a,[]), e2]=>  (0, E.Prod[ E.Tensor(a,[]), E.Apply(d, e2)]  )
| E.Prod((E.Tensor(a,[]))::e2)=>  (0, E.Prod[E.Tensor(a,[]), E.Apply(d, E.Prod e2)] )
| E.Prod es =>    (let
fun prod [e] = (E.Apply(d, e))
| prod(e1::e2)=(let val l= prod(e2) val m= E.Prod[e1,l]
val lr=e2 @[E.Apply(d,e1)]   val(b,a) =mkProd lr
in ( E.Add[ a, m] )
end)
| prod _= (E.Const(1.0))
in (1,prod es)
end)
| _=> (0,E.Apply(d,e))
(*end case*))

fun mkSumApply(E.Sum(c,E.Apply(d, e))) = (case e
of E.Tensor(a,[])=> (0,E.Const(0.0))
| E.Tensor _=> (0,E.Sum(c,E.Apply(d,e)))
| E.Field _ =>(0, E.Sum(c, E.Apply(d,e)))
| E.Const _=> (1,E.Const(0.0))
| E.Sub(e2, e3) =>(1, E.Sub(E.Sum(c,E.Apply(d, e2)), E.Sum(c,E.Apply(d, e3))))
| E.Prod((E.Epsilon c)::e2)=> mkEps(E.Apply(d,e))
| E.Prod[E.Tensor(a,[]), e2]=>  (0, E.Prod[ E.Tensor(a,[]), E.Sum(c,E.Apply(d, e2))]  )
| E.Prod((E.Tensor(a,[]))::e2)=>  (0, E.Prod[E.Tensor(a,[]), E.Sum(c,E.Apply(d, E.Prod e2))] )
| E.Prod es =>   (let
fun prod [e] = (E.Apply(d, e))
| prod(e1::e2)=(let val l= prod(e2) val m= E.Prod[e1,l]
val lr=e2 @[E.Apply(d,e1)]   val(b,a) =mkProd lr
in ( E.Add[ a, m] ) end)
| prod _= (E.Const(1.0))
in (1, E.Sum(c,prod es))  end)
| _=> (0,E.Sum(c,E.Apply(d,e)))
(*end case*))

(* Identity: (Epsilon ijk Epsilon ilm) e => (Delta jl Delta km - Delta jm Delta kl) e
The epsToDels Function searches for Epsilons in the expression, checks for this identity in all adjacent Epsilons and if needed, does the transformation.
The Function returns two separate list, 1 is the remaining list of Epsilons that have not be changed to deltas, and the second is the Product of the remaining expression.
Ex:(Epsilon_ijk Epsilon_ilm) Epsilon_stu e =>([Epsilon_stu], [Delta_jl,Delta_km,e -Delta_jm Delta_kl, e] )
This is useful since we can normalize the second list without having to normalize the epsilons again.
4(Eps Eps)
3( Delta_liDelta mj- Delta_mi Delta_lj)
Ai-
*)
16
17
18                     *)  fun prodAppPartial(es,p1)=(case es
19        of []      => raise Fail "Empty App Partial"
20        | [e1]     => E.Apply(E.Partial p1,e1)
21  fun epsToDels(E.Sum(count,E.Prod e))= let      | (e1::e2) => let
22      fun doubleEps((E.Epsilon (a,b,c))::(E.Epsilon(d,e,f))::es,eps,e3)=          val l= prodAppPartial(e2,p1)
23          let          val (_,e2')= F.mkProd[e1,l]
24            val (_,e1')=F.mkProd(e2@ [E.Apply(E.Partial p1, e1)])
(*Function is called when eps are being changed to deltas*)
fun createDeltas(i,s,t,u,v, e3)= let

(*remove index from original index list*)
(*currrent, left, sumIndex*)

fun rmIndex(_,_,[])=[]
| rmIndex([],[],cs)=cs
| rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)
| rmIndex(i::ix,rest ,(E.V c)::cs)=
if(i=c) then rmIndex(rest@ix,[],cs)
else rmIndex(ix,rest@[i],(E.V c)::cs)

val s'= rmIndex([i,s,t,u,v],[],count)
val s''=[E.V s, E.V t ,E.V u, E.V v]
val deltas= E.Sub(
E.Sum(s'',E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3)),
E.Sum(s'',E.Prod([E.Delta(E.V s,E.V v), E.Delta(E.V t,E.V u)]@e3)))

in (case (eps,s')
of ([],[]) =>(1,deltas)
|([],_)=>(1,E.Sum(s',deltas))
|(_,[])=>(1,E.Prod(eps@[deltas]))
|(_,_) =>(1, E.Sum(s', E.Prod(eps@[deltas])))
)
end

in if(a=d) then createDeltas(a,b,c,e,f, e3)
else if(a=e) then createDeltas(a,b,c,f,d, e3)
else if(a=f) then createDeltas(a,b,c,d,e, e3)
else if(b=d) then createDeltas(b,c,a,e,f, e3)
else if(b=e) then createDeltas(b,c,a,f,d,e3)
else if(b=f) then createDeltas(b,c,a,d,e,e3)
else if(c=d) then createDeltas(c,a,b,e,f,e3)
else if(c=e) then createDeltas(c,a,b,f,d,e3)
else if(c=f) then createDeltas(c,a,b,d,e,e3)
else (0,E.Const 0.0)
end
fun findeps(e,[])= (e,[])
| findeps(e,(E.Epsilon eps)::es)=  findeps(e@[E.Epsilon eps],es)
| findeps(e,es)= (e, es)

fun dist([],eps,rest)=(0,eps,rest)
| dist([e],eps,rest)=(0,eps@[e],rest)
| dist(c1::current,eps,rest)=let
val(i, exp)= doubleEps(c1::current,eps,rest)
in  (case i of 1=>(i,[exp],[E.Const 2.0])
|_=> dist(current, eps@[c1],rest))
end

val (es,rest)=findeps([],e)

in
dist(es,[],rest)
end

(*

(*The Deltas then need to be distributed over to the tensors in the expression e.
Ex.:Delta ij ,Tensor_j, e=> Tensor_i,e. The mkDelts function compares every Delta in the expression to the tensors in the expressions while keeping the results in the correct order.
This also returns a list of deltas and a list of the remaining expression.
*)

fun mkDel(e) = let
fun Del(i, [],x)= (i,[],x)
| Del(i, d,[])=(i, d,[])
| Del(i, (E.Delta(d1,d2))::d, (E.Tensor(id,[x]))::xs)=
if(x=d2) then (let
val(i',s,t)= Del(i+1,d, xs)
in Del(i',s, [E.Tensor(id, [d1])] @t) end)
else (let val (i',s,t)= Del(i,[E.Delta(d1,d2)],xs)
val(i2,s2,t2)= Del(i',d,[E.Tensor(id,[x])]@t)
in (i2,s@s2, t2) end )
| Del(i, (E.Delta(d1,d2))::d, (E.Field(id,[x]))::xs)=
if(x=d2) then (let
val(i',s,t)= Del(i+1,d, xs)
in Del(i',s, [E.Field(id, [d1])] @t) end)
else (let val (i',s,t)= Del(i,[E.Delta(d1,d2)],xs)
val(i2,s2,t2)= Del(i',d,[E.Field(id,[x])]@t)
in (i2,s@s2, t2) end )

| Del(i, d, t)= (i,d,t)
fun findels(e,[])= (e,[])
| findels(e,es)= let val del1= hd(es)
in (case del1
of E.Delta _=> findels(e@[del1],tl(es))
|_=> (e, es))
end
val(a,b)= findels([], e)
25      in      in
27      end      end
28        (* end case *))
29
30    (*rewritten Sum*)
31    fun mkSum(c1,e1)=(case e1
32        of E.Conv _   => (0,E.Sum(c1,e1))
33        | E.Field _   => (0,E.Sum(c1,e1))
34        | E.Probe _   => (0,E.Sum(c1,e1))
35        | E.Apply _   => (0,E.Sum(c1,e1))
36        | E.Delta _   => (0,E.Sum(c1,e1))
37        | E.Epsilon _ => (0,E.Sum(c1,e1))
38        | E.Tensor _  => (0,E.Sum(c1,e1))
39        | E.Neg e2    => (1,E.Neg(E.Sum(c1,e2)))
40        | E.Lift e    => (1,E.Lift(E.Sum(c1,e)))
41        | E.Sum(c2,e2)=> (1,E.Sum(c1@c2,e2))
42        | E.Sub (a,b) => (1,E.Sub(E.Sum(c1,a),E.Sum(c1,b)))
43        | E.Div (a,b) => (1,E.Div(E.Sum(c1,a),E.Sum(c1,b)))
45        | E.Prod p     =>F.filterSca(c1,p)
46        | E.Const _   => err("Sum of Const")
47        | E.Partial _ => err("Sum of Partial")
48        | E.Krn _     => err("Krn used before expand")
49        | E.Value _   => err("Value used before expand")
50        | E.Img _     => err("Probe used before expand")
51        (*end case*))
52
53  (*The Deltas are distributed over to the tensors in the expression e.  (*rewritten Apply*)
54   This function checks for instances of the dotProduct.  fun mkapply(d1,e1)=(case e1
55  Sum_2 (Delta_ij (A_i B_j D_k))=>Sum_1(A_i B_i) D_k      of E.Lift e   => (1,E.Const 0)
56  *)      | E.Prod []   => err("Apply of empty product")
57     fun checkDot(E.Sum(s,E.Prod e))= let      | E.Add []    => err("Apply of empty Addition")
58         fun dot(i,d,r, (E.Tensor(ida,[a]))::(E.Tensor(idb,[b]))::ts)=      | E.Conv(v, alpha, h, d2)    =>let
59                     if (a=b) then                          val E.Partial d3=d1
60                          dot(i-1,d@[E.Sum(1,E.Prod[(E.Tensor(ida,[a])), (E.Tensor(idb,[b]))])], [],r@ts)                          in (1,E.Conv(v,alpha,h,d2@d3)) end
61                     else dot(i,d, r@[E.Tensor(idb,[b])],(E.Tensor(ida,[a]))::ts)      | E.Field _   => (0,E.Apply(d1,e1))
62            |dot(i, d,r, [t])=dot(i,d@[t], [], r)      | E.Probe _   => (0,E.Apply(d1,e1))
63            |dot(i,d, [],[])= (i,d, [],[])      | E.Apply(E.Partial d2,e2)  => let
64            |dot(i,d, r, [])= dot(i,d, [], r)                          val E.Partial d3=d1
65            |dot(i, d, r, (E.Prod p)::t)= dot (i, d, r, p@t)                          in (1,E.Apply(E.Partial(d3@d2),e2)) end
66            |dot(i,d, r, e)= (i,d@r@e, [], [])      | E.Apply _   => raise Fail" Apply of non-Partial expression"
67        | E.Neg e2    => (1,E.Neg(E.Apply(d1,e2)))
68          val(i,d,r,c)= dot(s,[],[], e)      | E.Sum(c2,e2)=> (1,E.Sum(c2,E.Apply(d1,e2)))
69          val soln= (case d of [d1]=>d1      | E.Add e     => (1,E.Add (List.map (fn(a)=>E.Apply(d1,a)) e))
70                     |_=> E.Prod d)      | E.Sub (a,b) => (1,E.Sub(E.Apply(d1,a),E.Apply(d1,b)))
71          in E.Sum(i,soln) end      | E.Div (a,b) => (1,E.Div(E.Apply(d1,a),E.Apply(d1,b)))
72        |checkDot(e)= (e)      | E.Prod p =>let
73            val (pre, post)= F.filterField p
74            val E.Partial d3=d1
75            in F.mkProd(pre@[prodAppPartial(post,d3)])
76            end
77        | E.Const _   => err("Const without Lift")
78        | E.Tensor _  => err("Tensor without Lift")
79                  *)      | E.Delta _   => err("Apply of Delta")
80        | E.Epsilon _ => err("Apply of Eps")
81  fun reduceDelta(E.Sum(c,E.Prod p))=let      | E.Partial _ => err("Apply of Partial")
82        | E.Krn _     => err("Krn used before expand")
83        | E.Value _   => err("Value used before expand")
84        | E.Img _     => err("Probe used before expand")
85        (*end case*))
86
fun findDeltas(dels,rest,E.Delta d::es)= findDeltas(dels@[E.Delta d], rest, es)
| findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)
| findDeltas(dels,rest,es)=  (dels,rest,es)
87
88      fun rmIndex(_,_,[])=[]  (*rewritten probe*)
89          | rmIndex([],[],cs)=cs  fun mkprobe(e1,x)=(case e1
90          | rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)      of E.Lift e   => (1,e)
91          | rmIndex(i::ix,rest ,c::cs)=      | E.Prod []   => err("Probe of empty product")
92              if(i=c) then rmIndex(rest@ix,[],cs)      | E.Prod p    => (1,E.Prod (List.map (fn(a)=>E.Probe(a,x)) p))
93              else rmIndex(ix,rest@[i],c::cs)      | E.Apply _   => (0,E.Probe(e1,x))
94        | E.Conv _    => (0,E.Probe(e1,x))
95        | E.Field _   => (0,E.Probe(e1,x))
97        | E.Sum(c,e') => (1,E.Sum(c,E.Probe(e',x)))
98        | E.Div (a,b) => (1,E.Div(E.Probe(a,x),E.Probe(b,x)))
99        | E.Sub (a,b) => (1,E.Sub(E.Probe(a,x),E.Probe(b,x)))
100        | E.Neg e'    => (1,E.Neg(E.Probe(e',x)))
101        | E.Const _   => err("Const without Lift")
102        | E.Tensor _  => err("Tensor without Lift")
103        | E.Delta _   => err("Probe of Delta")
104        | E.Epsilon _ => err("Probe of Eps")
105        | E.Partial _ => err("Probe Partial")
106        | E.Probe _   => err("Probe of a Probe")
107        | E.Krn _     => err("Krn used before expand")
108        | E.Value _   => err("Value used before expand")
109        | E.Img _     => err("Probe used before expand")
110    (*end case*))
111
fun distribute(change,d,dels,[],done)=(change,dels@d,done)
| distribute(change,[],[],e,done)=(change,[],done@e)
| distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=
if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Tensor(id,[i])])
else distribute(change,ds,dels@[E.Delta(i,j)],E.Tensor(id,[tx])::es,done)
| distribute(change,d,dels,e::es,done)=distribute(change,dels@d,[],es,done@[e])
112
val (dels,eps,es)=findDeltas([],[],p)
val (change,dels',done)=distribute([],dels,[],es,[])
val index=rmIndex(change,[],c)
113
in
(change, E.Sum(index,E.Prod (eps@dels'@done)))
end
114
115
116    (*fun K gg=String.concatWith "," (List.map (fn (E.V e1,_,_)=> (Int.toString(e1))) gg)*)
117    fun K _= " "
118    fun Kt gg=List.map (fn e1=> print(String.concat["[", (K e1),"]"])) gg
119
120  (*Apply normalize to each term in product list  (*Apply normalize to each term in product list
121  or Apply normalize to tail of each list*)  or Apply normalize to tail of each list*)
122  fun normalize (Ein.EIN{params, index, body}) = let  fun normalize (Ein.EIN{params, index, body}) = let
123         (* val _ = print(String.concat["\n IN NORMALIZE@", P.printbody(body),"@\n"])*)
124        val changed = ref false        val changed = ref false
125          val sumIndex=ref []
126
127        fun rewriteBody body = (case body        fun rewriteBody body = (case body
128               of E.Const _=> body               of E.Const _=> body
129                | E.Tensor _ =>body                | E.Tensor _ =>body
130                | E.Field _=> body                | E.Field _=> body
| E.Kernel _ =>body
131                | E.Delta _ => body                | E.Delta _ => body
| E.Value _ =>body
132                | E.Epsilon _=>body                | E.Epsilon _=>body
133                | E.Conv _      => body
134                | E.Partial _   => body
135                | E.Krn _       => raise Fail"Krn before Expand"
136                | E.Img _       => raise Fail"Img before Expand"
137                | E.Value _     => raise Fail"Value before Expand"
138
139                    (*************Algebraic Rewrites **************)
140                | E.Neg(E.Neg e)    => rewriteBody e
141                | E.Neg e => E.Neg(rewriteBody e)                | E.Neg e => E.Neg(rewriteBody e)
142                | E.Add es => let val (b,a)= mkAdd(List.map rewriteBody es)              | E.Lift e          => E.Lift(rewriteBody e)
143                     in if (b=1) then ( changed:=true;a) else a end              | E.Add es          => let val (change,body')= F.mkAdd(List.map rewriteBody es)
144                       in if (change=1) then ( changed:=true;body') else body' end
145                | E.Sub(a, E.Field f)=> (changed:=true;E.Add[a, E.Neg(E.Field(f))])
149                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)
150                | E.Div(E.Div(a,b),E.Div(c,d))  => rewriteBody(E.Div(E.Prod[a,d],E.Prod[b,c]))
151                | E.Div(E.Div(a,b),c)           => rewriteBody (E.Div(a, E.Prod[b,c]))
152                | E.Div(a,E.Div(b,c))           =>  rewriteBody (E.Div(E.Prod[a,c],b))
153                | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)                | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)
| E.Partial _=>body
| E.Conv (V, alpha)=> E.Conv(rewriteBody V, alpha)
| E.Probe(u,v)=>  E.Probe(rewriteBody u, rewriteBody v)
| E.Image es => E.Image(List.map rewriteBody es)
154
155                  (*Product*)                  (**************Apply, Sum, Probe**************)
156                | E.Apply(E.Partial [],e)=> e
157                | E.Apply(E.Partial d1, e1)=>let
158                    val e2 = rewriteBody e1
159                    val (c,e3)=mkapply(E.Partial d1,e2)
160                    in (case c of 1=>(changed:=true;e3)| _ =>e3 (*end case*))
161                    end
162                | E.Apply _=> raise Fail" Not well-formed Apply expression"
163                | E.Sum([],e)=> (changed:=true;rewriteBody e)
164                | E.Sum(c,e)=>let
165                    val ref x=sumIndex
166                    val c'=[c]@x
167                    val e'=(sumIndex:=c';rewriteBody e)
168                    val ref s=sumIndex
169                    val z=hd(s)
170                    val (cng,e2)=(sumIndex:=tl(s);mkSum(z,e'))
171                    in (case cng
172                        of 1=> (changed:=true;e2)
173                        |_=> e2
174                        (*end case*))
175                    end
176                  | E.Probe(u,v)=>  let
177                    val (c',b')=mkprobe(rewriteBody u,rewriteBody v)
178                    in (case c'
179                        of 1=> (changed:=true;b')
180                        |_=> b'
181                        (*end case*))
182                    end
183
184                    (*************Product**************)
185                  | E.Prod [] => raise Fail"missing elements in product"
186                | E.Prod [e1] => rewriteBody e1                | E.Prod [e1] => rewriteBody e1
188                    (changed :=true; E.Div(E.Prod([e2]@e4), e3 ))
190                       (changed := true; E.Add(List.map (fn e=> E.Prod([e]@e3)) e2))
192                     (changed := true; E.Add(List.map (fn e=> E.Prod([e1, e]@e3)) e2))                     (changed := true; E.Add(List.map (fn e=> E.Prod([e1, e]@e3)) e2))
193                | E.Prod(e1::(E.Sub(e2,e3))::e4)=>                | E.Prod((E.Sub(e2,e3))::e4)=>
194                    (changed :=true; E.Sub(E.Prod([e2]@e4), E.Prod([e3]@e4 )))
195                  | E.Prod(e1::E.Sub(e2,e3)::e4)=>
196                     (changed :=true; E.Sub(E.Prod([e1, e2]@e4), E.Prod([e1,e3]@e4 )))                     (changed :=true; E.Sub(E.Prod([e1, e2]@e4), E.Prod([e1,e3]@e4 )))
| E.Prod [E.Partial r1,E.Conv(f,deltas)]=>
(changed :=true;E.Conv(f,deltas@r1))
| E.Prod (E.Partial r1::E.Conv(f,deltas)::ps)=>
(changed:=true; E.Prod([E.Conv(f,deltas@r1)]@ps))
197
198
199                | E.Prod(e::es)=>let
200                      val e'=rewriteBody e                  (*************Product EPS **************)
201                      val e2=rewriteBody(E.Prod es)
202                      in(case e2 of E.Prod p'=> E.Prod([e']@p')                | E.Prod(E.Epsilon(i,j,k)::E.Apply(E.Partial d,e)::es)=>let
203                          |_=>E.Prod [e',e2])                   val change= G.matchEps(0,d,[],[i,j,k])
204                     in case (change,es)
205                    of (1,_) =>(changed:=true; E.Const 0)
206                        | (_,[]) =>E.Prod[E.Epsilon(i,j,k),rewriteBody (E.Apply(E.Partial d,e))]
207                        |(_,_)=> let
208                            val a=rewriteBody(E.Prod([E.Apply(E.Partial d,e)]@ es))
209                            val (_,b)=F.mkProd [E.Epsilon(i,j,k),a]
210                            in b end
211                    end
212                  | E.Prod(E.Epsilon(i,j,k)::E.Conv(V,alpha, h, d)::es)=>let
213
214                    val change= G.matchEps(0,d,[],[i,j,k])
215                    in case (change,es)
216                        of (1,_) =>(changed:=true; E.Const 0)
217                        | (_,[]) =>E.Prod[E.Epsilon(i,j,k),E.Conv(V,alpha, h, d)]
218                        | (_,_) =>let
219                            val a=rewriteBody(E.Prod([E.Conv(V,alpha, h, d)]@ es))
220                            val (_,b) = F.mkProd [E.Epsilon(i,j,k),a]
221                            in b end
222                     end                     end
223
(*Apply*)
| E.Apply(e1,e2)=>E.Apply(rewriteBody e1, rewriteBody e2)
224
225                  | E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>
226                        if(e2=i1 andalso e3=i2) then (changed :=true;E.Const(0))
227                        else body
228
229
230                (* Sum *)              | E.Prod(E.Epsilon eps1::ps)=>
231                | E.Sum([],e)=> rewriteBody e                  let
232                     | E.Sum(_,E.Const c)=>(changed:=true;E.Const c)
233                | E.Sum(c,(E.Add l))=> (changed:=true;E.Add(List.map (fn e => E.Sum(c,e)) l))                  val ref x=sumIndex
234                | E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>                  val (i,s',e,rest)=G.epsToDels(x,body)
let val (i,e,rest)=epsToDels(body)
235                     in (case (i, e,rest)                     in (case (i, e,rest)
236                     of (1,[e1],_) =>(changed:=true;e1)                  of (1,[e1],_) =>(changed:=true;sumIndex:=s';e1)
237                          |(0,eps,[])=>body                          |(0,eps,[])=>body
238                          |(0,eps,rest)=>(let                      | _ => let
239                              val p'=rewriteBody(E.Prod rest)                              val p'=rewriteBody(E.Prod rest)
240                              val p''= (case p' of E.Prod p=>p |e=>[e])                              val p''= (case p' of E.Prod p=>p |e=>[e])
241                              in E.Sum(c, E.Prod (eps@p'')) end                          val(_,b)= F.mkProd (e@p'')
242                              )                          in b end
243                          |_=>body                          (*end case*))
244                     ) end                   end
245                | E.Sum(c, E.Prod(E.Delta d::es))=>let              | E.Prod(E.Sum(c1,E.Prod(E.Epsilon e1::es1))::E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es)=>let
246                      val (change,body')=reduceDelta(body)                  val ref x=sumIndex
247                     in (case change of []=>body'|_=>(changed:=true;body')) end
248                | E.Sum(c,e)=>E.Sum(c,rewriteBody e)
249                    val m= Kt x
250
251                    val c'= [c1@c2]@x
252                    val (i,s',e,rest)=G.epsToDels(c', E.Prod([E.Epsilon e1, E.Epsilon e2]@es1@es2@es))
253                     val gsg=Kt s'
254
255
256                    in (case (i, e,rest)
257                        of (1,[e1],_)=> (changed:=true;sumIndex:=s';let
258                            val ss=List.nth(s',((length s')-2))
259                            in
260                                E.Sum(ss,e1) end )
261                        | _=>let
262                            val eA=rewriteBody(E.Sum(c1,E.Prod(E.Epsilon e1::es1)))
263                            val eB=rewriteBody(E.Prod(E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es))
264                            val (_,e)=F.mkProd([eA,eB])
265                            in e
266                            end
267                        (*end case*))
268                    end
269
270                | E.Prod(E.Delta d::es)=>let
271                    val (pre',eps, dels,post)= F.filterGreek(E.Delta d::es)
272                    val ref x=sumIndex
273                    val (change,i',a)=G.reduceDelta(x, eps, dels, post)
274
275                    in (case (change,a)
276                        of (0, _)=> E.Prod [E.Delta d,rewriteBody(E.Prod es)]
277                        | (_, E.Prod p)=>let
278                            val (_, p') = F.mkProd p
279                            in (changed:=true;sumIndex:=i';p') end
280                        | _ => (changed:=true;sumIndex:=i';a )
281              (*end case*))              (*end case*))
282                        end
283
284        fun loop body = let                | E.Prod[e1,e2]=> let val (_,b)=F.mkProd[rewriteBody e1, rewriteBody e2] in b end
285                  | E.Prod(e::es)=>let
286                        val e'=rewriteBody e
287                        val e2=rewriteBody(E.Prod es)
288                        val(_,b)=(case e2
289                            of E.Prod p'=> F.mkProd([e']@p')
290                            |_=>F.mkProd [e',e2])
291                    in b
292                       end
293
294                (*end case*))
295
296                fun loop(body ,count) = let
297              val body' = rewriteBody body              val body' = rewriteBody body
298
299              in              in
300                if !changed                if !changed
301                     then (changed := false; (*print " \n \t => \n \t ";print( P.printbody body');print "\n";*)loop body')                  then let
302                  else body'                      val _= (case testing
303                            of 1=> (print(String.concat["\nN =>",Int.toString(count),"--",P.printbody(body')]);1)
304                            | _=> 1)
305                        in
306                            (changed := false ;sumIndex:=[];loop(body',count+1))
307              end              end
308      val b = loop body                  else (body',count)
309                end
310
311        val (b,count) = loop(body,0)
312        val _ =(case testing
313            of 1 => (print(String.concat["\n out of normalize \n",P.printbody(b),"\n    Final CounterXX:",Int.toString(count),"\n\n"]);1)
314            | _=> 1
315            (*end case*))
316      in      in
317      ((Ein.EIN{params=params, index=index, body=b}))                  (Ein.EIN{params=params, index=index, body=b},count)
318      end      end
319  end  end
320
321
322
323  end (* local *)  end (* local *)

Legend:
 Removed from v.2450 changed lines Added in v.2605